The Role of Student Activities in Supporting the Development of Children in Orphanages - Chua, Jovellysia Trecy; Lee, Sherlene; Tjendra, Melda; Tania, Jessica; Suhendra, Jonathan Jordan; Natalia, Lisa; Putri, Ayesha Nashwa Ferya; Morales, Abel; Fitriyah, Olla; Indah, Friderika; Darwan, Arya Putra Lievi; Febrianti, Della; Suyani, Suyani; Christine, Alice Yolanda; Ritonga, Muhammad Iuan Furqon; Habibah, Zahwa Rheina; Kezhiandra, Gabby (Journal of Education Technology Information Social Sciences and Health, 2024)
This study examines the role of student activities in supporting the development of children in orphanages. Using a qualitative approach with a case study design, the research involved in-depth interviews, participant observation, and document analysis, focusing on academic, emotional, and social aspects. Through brief visits, students conducted various activities such as education, ice-breaking, and the development of a mini-library. The findings show that student activities can enhance children's learning motivation, cognitive skills, and self-confidence. Additionally, these activities also strengthen empathy and social communication skills. Despite the significant positive impact, the limited duration of the visits poses a challenge in creating long-term changes. Therefore, this study recommends increasing the frequency of activities, developing long-distance mentoring programs, and collaborating with local educational institutions. These suggestions are expected to enhance the effectiveness of student programs in supporting the development of orphanage children and promoting social awareness among students.